Effects of authentic leadership, affective commitment and job resourcefulness on employees' creativity and individual performance. Issue 8 (7th November 2016) - Semedo, Ana Suzete Dias; Coelho, Arnaldo Fernandes Matos; Ribeiro, Neuza Manuel Pereira
Abstract : Purpose: The purpose of this paper is to report the findings of a study examining the relationship between authentic leadership (AL), attitudes and employees' behaviours. More specifically, how AL influences affective commitment, job resourcefulness and creativity, which, in turn, influence individual performance. Design/methodology/approach: Empirical research has analysed the data from a questionnaire administered to a sample of 543 employees belonging to various public and private organisations in Cape Verde. The model was tested using structural equation modelling. Findings: The results reveal that AL influences employees' attitudes (affective commitment and job resourcefulness) and their creativity, affective commitment and job resourcefulness predict the employees' creativity, and job resourcefulness and creativity predict individual performance. Practical implications: The results from this study can help managers to understand how to increase employees' creativity and performance through AL, affective commitment and job resourcefulness. Indirectly, the study also suggests that organisations should focus on selecting leaders with authentic features and implement appropriate training activities, coaching and development that aim to increase AL since this may well result in a positive impact on employees' attitudes and behaviours. Originality/value: The originality of this study is that it focusses on the integration of the five concepts, AL, affective commitment, job resourcefulness, creativity and individual performance, in a single study, providing a model that depicts the chain of effects between AL, employees' attitudes, employees' creativity and individual performance.